Best Answer

Points: (7, 3) and (-6, 1)

Midpoint: (0.5, 2)

Slope: 2/13

Perpendicular slope: -13/2

Equation: y-2 = -13/2(x-0.5) => 2y-4 = -13(x-0.5) => 2y = -13x+10.5

Perpendicular bisector equation in its general form: 13x+2y -10.5 = 0

Q: What is the perpendicular bisector equation of the line joined by the points of 7 3 and -6 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

8

Points: (s, 2s) and (3s, 8s) Midpoint: (2s, 5s) Slope: 3 Perpendicular slope: -1/3 Perpendicular equation: y-5s = -1/3(x-2s) => 3y-15s = -x+2s => 3y = -x+17s Perpendicular bisector equation in its general form: x+3y-17s = 0

Points: (-2, 3) and (1, -1) Midpoint: (-0.5, 1) Slope: -4/3 Perpendicular slope: 4/3 Equation: 3y = -4x+1 Perpendicular bisector equation: 4y = 3x+5.5

8

End points: (3, 5) and (7, 7) Midpoint: (5, 6) Slope: 1/2 Perpendicular slope: -2 Perpendicular bisector equation: y-6 = -2(x-5) => y = -2x+16

Related questions

Points: (-2, 5) and (-8, -3) Midpoint: (-5, 1) Slope: 4/3 Perpendicular slope: -3/4 Perpendicular equation: y-1 = -3/4(x--5) => 4y = -3x-11 Perpendicular bisector equation in its general form: 3x+4y+11 = 0

Points: (-1, 3) and (-2, -5) Midpoint: (-3/2, -1) Slope: 8 Perpendicular slope: -1/8 Perpendicular bisector equation: y--1 = -1/8(x--3/2) => y = -1/8x-19/16

Points: (-2, 4) and (-4, 8) Midpoint: (-3, 6) Slope: -2 Perpendicular slope: 1/2 or 0.5 Perpendicular bisector equation: y-6 = 0.5(x--3) meaning y = 0.5x+7.5

8

Points: (-1, -6) and (5, -8) Midpoint: (2, -7) Perpendicular slope: 3 Perpendicular bisector equation: y = 3x -13

Points: (s, 2s) and (3s, 8s) Midpoint: (2s, 5s) Slope: 3 Perpendicular slope: -1/3 Perpendicular equation: y-5s = -1/3(x-2s) => 3y-15s = -x+2s => 3y = -x+17s Perpendicular bisector equation in its general form: x+3y-17s = 0

Points: (3,-4) and (-1, -2) Midpoint: (1,-3) Slope: -1/2 Perpendicular slope: 2 Perpendicular bisector equation in slope intercept form: y = 2x-5

Points: (-2, 3) and (1, -1) Midpoint: (-0.5, 1) Slope: -4/3 Perpendicular slope: 4/3 Equation: 3y = -4x+1 Perpendicular bisector equation: 4y = 3x+5.5

8

Points: (-1, 4) and (3, 8) Midpoint (1, 6) Slope: 1 Perpendicular slope: -1 Perpendicular bisector equation: y-6 = -1(x-1) => y = -x+7

End points: (3, 5) and (7, 7) Midpoint: (5, 6) Slope: 1/2 Perpendicular slope: -2 Perpendicular bisector equation: y-6 = -2(x-5) => y = -2x+16

Points: (s, 2s) and (3s, 8s) Midpoint: (2s, 5s) Slope: 3 Perpendicular slope: -1/3 Perpendicular equation: y -5s = -1/3(x -2s) => 3y = -x +17s Perpendicular bisector equation in its general form: x +3y -17s = 0